Effectiveness of virtual manipulative teaching method in enhancing year four pupils’ understanding of fractions / Kavitha Karbal Singh - Kavitha , Karbal Singh (2020)

(untitled)
Fractions are common numerical representations in mathematics. However, they seem to be a complicated mathematical concept to master, particularly among school pupils. Pupils have a hard time studying fraction due to insufficient understanding of the concept. An effective teaching method is therefore essential for the teaching and learning of this particular component. The purpose of this study is to determine the effectiveness of the virtual manipulative teaching method in improving the understanding of fraction among Primary Year Four pupils. Essentially a quasi-experimental research, the method used was a non-equivalent, control group pretest-posttest approach. A total of 80 pupils from a government primary school in Selangor were categorized into two groups in which the first group was the experimental group (N = 40) and second was the control group (N = 40). The experimental group was taught the concept of fraction using the virtual manipulative method, while the control group was taught the concept of fraction without using the method. Both groups were tested before and after the experiment using the Test for Understanding of Concept of Fraction. The result of the paired t-test of the experimental group for pre and posttest scores shows that the pupils’ understanding of fraction increased significantly after the experiment i.e. t (39) = 18.14, p < .0005. Whereas, the independent posttest mean experimental score i.e. M = 18.83, SD = 2.872 and control group i.e. M = 14.18, SD=4.242 shows that the pupils’ understanding the concept of fraction is noticeably different from the control group i.e. t (78) = -5.79, p < .05. Thus, it has been concluded that the virtual manipulative method is successful in improving Year Four pupils' understanding of the concept of fraction.